The Feasibility of Puncak Damar and Tanjung Duriat Ecotourism as Tourist Destination Areas - Aziza, Nadya Nur; Djuwendah, Endah (Journal of Business on Hospitality and Tourism, 2019)
Jatigede Reservoir area has potential to be a Tourist Destination Area. This area has two ecotourism that are Puncak Damar and Tanjung Duriat. The area will be used as a Tourism Special Economic Zone (Kawasan Ekonomi Khusus). This research purpose is to find out how the feasibility of Puncak Damar and Tanjung Duriat Ecotourism as tourist destinations. The design used is qualitative with a case research approach. The result of the research showes that Puncak Damar and Tanjung Duriat have not fulfill the principle of ecotourism. Puncak Damar Ecotourism has attractions, (1) the views of Jatigede Reservoir, (2) taking pictures at viewdeck, (3) camping, (4) offroad. While in Tanjung Duriat, that are (1) the view of the Jatigede Reservoir, (2) taking photos in tree towers, (3) camping, (4) fishing, (5) boating. In terms of accessibility, the road conditions of both ecotourism are damaged and rocky and there is no public transportation. The facilities of the infrastructure in both ecotourism are not yet complete. The obstacles in Puncak Damar Ecotourism are (1) damaged road conditions, (2) no clean water, (3) no food stall that operate, (4) relations between managers. In Tanjung Duriat there obstacles are: (1) damaged road conditions, (2) no electricity system, (3) relations between managers. Both of these ecotourism are still not feasible for tourist destinations. It is because there are still many attractions that cannot support tourism activities at Puncak Damar and Tanjung Duriat Ecotourism objects.